Understanding deradicalization methods, tools and programs for countering violent extremism - Koehler, Daniel (Contemporary terrorism studies, 2017)
This book provides a comprehensive guide to the different aspects of deradicalization theories, programs and methods. It analyzes the practical and theoretical aspects of deradicalization programs and the methods being employed to bring extremists and terrorist back to a non-violent life. In essence, this work enables the reader to identify how, when and why deradicalization programs work, how they can be built and structured, and to identify their limitations.